KAJIAN PEMANFAATAN POMPA AIR BANTUAN PEMERINTAH UNTUK MENUNJANG IRIGASI PERTANIAN DI KABUPATEN - Vilian F. Tumober; Leo H. Kalesaran; David P. Rumambi (Universitas Sam Ratulangi, 2023)
AbstactThis research was conducted to determine the feasibility of using pumps infulfilling water for plants so that the farming system. Support for groundwaterirrigation by using pumps for farming activities in Minahasa Regency. Based onthe description above, research will be carried out on